International Comparisons of Trends in Economic Well-being - Lars Osberg; Andrew Sharpe (Luxembourg Income Study (LIS), 2000)
This objective of this paper is to develop an index of economic well being for selected OECD countries for the period 1980 to 1996 and to compare trends in economic well being. We argue that the economic well being of a society depends on the level of average consumption flows, aggregate accumulation of productive stocks, inequality in the distribution of individual incomes and insecurity in the anticipation of future incomes. However, the weights attached to each component will vary, depending on the values of different observers. This paper argues that public debate would be improved if there is explicit consideration of the aspects of economic well-being obscured by average income trends and if the weights attached to these aspects were made visible and were open for discussion. The four components of economic well-being which are identified are: (1) effective per capita consumption flows, which includes consumption of marketed goods and services, and effective per capita flows of unmarketed goods and services and changes in leisure; (2) net societal accumulation of stocks of productive resources, including net accumulation of tangible capital and housing stocks, net accumulation of human capital and R investment, environmental costs, and net change in level of foreign indebtedness; (3) income distribution, as indicated by the Gini index of inequality, and depth and incidence of poverty; and (4) economic security from unemployment, ill health, single parent poverty and poverty in old age. Although estimates of the overall index and the subcomponents are presented for 1980- 1996 for 14 countries, the limited number of years for micro-data files from the Luxembourg Income Study make some estimates problematic - hence our major focus is trends in economic well-being in the USA, UK, Canada, Australia, Norway and Sweden. (Additional tables and charts in 242a.pdf.)
Keywords: 330; Lebensstandard; Einkommensverteilung; OECD-Staaten